Taxonomic revision of the Ophidion holbrookii Putnam, 1874 (Ophidiiformes: Ophidiidae) species complex, with description of a new species from Brazil - Rotundo, Matheus Marcos; Caires, Rodrigo Antunes; Oliveira, Claudio [UNESP]; Kuranaka, Mariana [UNESP]; de Figueiredo-Filho, Jessé Miranda; Marceniuk, Alexandre Pires (Magnolia Press, 2023)
This study integrates morphological and molecular data to redefine the taxonomic limits of Ophidion holbrookii, as well as its geographic ranges, with the description of a new species from the eastern and southeastern coast of Brazil, South America. Ophidion zavalai n. sp. is described based on variations related to ontogeny and sexual development of swim bladder and sonic apparatus, which are likely important traits for species recognition. The description of O. zavalai n. sp. and the redefinition of distribution limits of O. holbrookii corroborate the existence of different complex species in the western Atlantic, revealing important gaps of knowledge regarding morphological variation and species habits. Ophidion zavalai n. sp. is the first species of Ophidion described from the southwestern Atlantic Ocean and contributes to evidence of a distinct coastal fauna in Brazil and surrounding areas of Argentina province.
Keywords: Brazilian coast; Gas bladder; mitochondrial gene; sonic apparatus; western Atlantic